The bushmeat trade and livelihoods in southern Benin: An exploratory survey - SOGBOHOSSOU, ETOTEPE A.; Kassa, Barthelemy (My University, 2016)
Bushmeat is among the multiple and most important products provided by forests to human populations. In this article the authors present the results of an exploratory survey in southern part of Republic of Benin. This exploratory survey aims at assessing the characteristics of the bushmeat trade and evaluate its contribution to local stakeholders' income. The questionnaire survey and observations revealed that four species are more sought by hunters and consumers: francolin, Gambian rat, hare and cane rat. These animals can be found in farms, tree plantations or the Lama forest core area showing the importance of the neighboring protected area to local populations' livelihoods. The bushmeat trade effectively improves the income of stakeholders. However it could not be encouraged because it is illegal and it impacts negatively wildlife and habitat dynamics. It is then critical to apply the laws and regulate this trade. It is also essential to develop activities that provide income to local communities and provide legally wildlife proteins for consumption. Further research on the patterns of this trade and its real impact on the biodiversity is necessary.
Keywords: Bushmeat traede; Lama forest; revenue